2021
DOI: 10.3389/fimmu.2021.654080
|View full text |Cite
|
Sign up to set email alerts
|

Bispecific Antibody PD-L1 x CD3 Boosts the Anti-Tumor Potency of the Expanded Vγ2Vδ2 T Cells

Abstract: Vγ2Vδ2 T cell-based immunotherapy has benefited some patients in clinical trials, but the overall efficacy is low for solid tumor patients. In this study, a bispecific antibody against both PD-L1 and CD3 (PD-L1 x CD3), Y111, could efficiently bridge T cells and PD-L1 expressing tumor cells. The Y111 prompted fresh CD8+ T cell-mediated lysis of H358 cells, but spared this effect on the fresh Vδ2+ T cells enriched from the same donors, which suggested that Y111 could bypass the anti-tumor capacity of the fresh V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…The mean EC 50 values for Vg2 x PD-L1 binding to CHO-PD-L1, SKOV3, and H1975 were 1.444 nM, 0.594 nM, and 1.687 nM, respectively (Figure 1B, Figure 2). Both Vg2 x PD-L1 bsAb and PD-L1 mAb had a similar affinity to the cellular surface PD-L1 (Figure 1B), due to these two antibodies having the same variable regions for PD-L1 binding (23). Furthermore, we determined the PD-L1 expression scores for a series of target tumor cells using Vg2 x PD-L1 bsAb, which confirmed that Vg2 x PD-L1 exhibited potent affinity toward tumor cells with variable PD-L1 expression levels (Supplementary Figure 2).…”
Section: Design Generation and Characterization Of Vg2 X Pd-l1mentioning
confidence: 94%
See 2 more Smart Citations
“…The mean EC 50 values for Vg2 x PD-L1 binding to CHO-PD-L1, SKOV3, and H1975 were 1.444 nM, 0.594 nM, and 1.687 nM, respectively (Figure 1B, Figure 2). Both Vg2 x PD-L1 bsAb and PD-L1 mAb had a similar affinity to the cellular surface PD-L1 (Figure 1B), due to these two antibodies having the same variable regions for PD-L1 binding (23). Furthermore, we determined the PD-L1 expression scores for a series of target tumor cells using Vg2 x PD-L1 bsAb, which confirmed that Vg2 x PD-L1 exhibited potent affinity toward tumor cells with variable PD-L1 expression levels (Supplementary Figure 2).…”
Section: Design Generation and Characterization Of Vg2 X Pd-l1mentioning
confidence: 94%
“…The bsAbs, including Vg2 x PD-L1 and Vg2 x Null, were generated similarly to Y111 described previously by Yang et al (23). Briefly, the expression plasmids for Vg2 x PD-L1 and Vg2 x Null were synthesized and verified by sequencing in AuGCT Biotech (Wuhan, China).…”
Section: Generation Of the Recombinant Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Programmed cell death 1 ligand-targeted bispecific antibodies have also shown activation of Vγ9Vδ2 T cells, leading to tumor growth inhibition in vivo. 40 γδ T cells can also serve as vessels for chimeric antigen receptors (CARs) and TCRs. For example, an anti-chondroitinsulfate-proteoglycan 4 CAR showed equivalent tumor activity, yet less cytokine release than αβ T cells in an in vitro setting, suggesting a safer alternative to conventional engineered T cells against melanoma cell lines.…”
Section: Preclinical-stage γδ T-cell-based Actsmentioning
confidence: 99%
“…Programmed cell death 1 ligand–targeted bispecific antibodies have also shown activation of Vγ9Vδ2 T cells, leading to tumor growth inhibition in vivo. 40 …”
Section: Preclinical-stage γδ T-cell–based Actsmentioning
confidence: 99%